The Prevalence and Underreporting of Needlestick Injuries among Dental Healthcare Workers in Pakistan: A Systematic Review - Mehak Pervaiz; Ruth Gilbert; Nasreen Ali (International Journal of Dentistry)
Needlestick injuries (NSIs) are a major occupational health problem among dental healthcare workers (HCWs) in Pakistan, which places them at a significant risk of acquiring blood-borne infections. However, not all NSIs are reported, leading to an underestimation of the actual prevalence. The harmful impacts of NSIs on the healthcare delivery necessitate an urgent need to measure its actual prevalence. Objectives. The aim of this study was to review literature to estimate the prevalence and reporting rates of NSIs among dental-HCWs in Pakistan. Methods. 713 potentially relevant citations were identified by electronic databases and hand searching of articles. Nine primary studies were subsequently identified to be included in the review. Results. The results of the included studies indicate that the prevalence of NSIs among Pakistani dental-HCWs was between 30% and 73%. The rate of reporting of NSIs was between 15% and 76%, and the most common reason was found to be the lack of awareness regarding the reporting system, or of the need to report NSIs. Conclusion. It is evident from the review of the included studies that there is a significantly high prevalence and a low rate of reporting of NSIs among dental-HCWs in Pakistan, suggesting the need to setup an occupational health department in dental settings, for preventing, managing, recording, and monitoring NSIs.